Nurturing innovative thinkers - Nurul Hazlina, Noordin; Mohd Raizalhilmy, Mohd Rais (Pejabat Naib Canselor, 2016)
A total of 264 teams from 25 institutes of higher learning (IHLs) took part in the Innovate Malaysia Design Competition (IMDC) 2016 but only 45 made it through to the grand finale which was held in Equatorial Hotel in Penang on August 9, 2016.